2010
DOI: 10.1016/j.atherosclerosis.2009.09.030
|View full text |Cite
|
Sign up to set email alerts
|

The associations of interleukin-6 (IL-6) and downstream inflammatory markers with risk of cardiovascular disease: The Caerphilly Study

Abstract: a b s t r a c tObjectives: Interleukin-6 (IL-6) is a key pro-inflammatory cytokine which mediates expression of several 'downstream' inflammatory markers and may play a role in atherothrombosis. However, it is not yet known whether IL-6 plays a role in mediating the associations of each marker with risk of coronary heart disease (CHD) or ischaemic stroke (IS). Methods and results:We examined the role of IL-6 and several "downstream" markers of inflammation (leucocyte counts, plasma and serum viscosity, fibrino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
40
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 26 publications
6
40
2
1
Order By: Relevance
“…Of note, the magnitude of the multivariable association of hs-CRP with ischemic stroke in our study was similar to that from a recent meta-analysis of individual participant data (OR, 1.20 versus hazard ratio, 1.27 per SD increment in the log-transformed variable). 20 The lack of a significant association between IL-6 and ischemic stroke in the present study is consistent with results of the above mentioned Caerphilly Study, 21 but contrasts with findings in older populations. 8,22,23 IL-6 concentration varies with time and, therefore, regression dilution bias may have contributed to the lack of a significant association with ischemic stroke in the present study.…”
Section: Associationssupporting
confidence: 78%
“…Of note, the magnitude of the multivariable association of hs-CRP with ischemic stroke in our study was similar to that from a recent meta-analysis of individual participant data (OR, 1.20 versus hazard ratio, 1.27 per SD increment in the log-transformed variable). 20 The lack of a significant association between IL-6 and ischemic stroke in the present study is consistent with results of the above mentioned Caerphilly Study, 21 but contrasts with findings in older populations. 8,22,23 IL-6 concentration varies with time and, therefore, regression dilution bias may have contributed to the lack of a significant association with ischemic stroke in the present study.…”
Section: Associationssupporting
confidence: 78%
“…We confirmed that IL-6 levels are investigated with composite CVD incidence, 3,12,13,21,22 stroke incidence [22][23][24] and recurrence, 25,26 mortality, 26 or prognosis after stroke. 27 However, the results of only a few clinical studies on initial stroke incidence remain controversial.…”
Section: Discussionsupporting
confidence: 55%
“…The Health ABC Study demonstrated that IL-6, but not hsCRP or tumor necrosis factor-α, predict stroke incidence in elderly populations without prior CVD. 23 In contrast, both the PROSPER 24 and Caerphilly 22 studies confirmed that no inflammatory markers, including IL-6, 22,24 hsCRP, 22,24 and IL-18, 24 showed independent associations and discrimination of stroke risk. The significance of inflammation marker in these previous studies has not been consistently shown in terms of discriminatory ability, judged from the C-statistic.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…IL-1ß, also produced mainly by macrophages and the action of which overlaps partly with TNF, induces metalloproteinases, nitric oxide synthase, and adhesion molecules. Moreover, IL-6 and TNF-· have been proven to be clinical markers to identify and track inflammation (27)(28)(29)(30). Targeting inflammatory cytokines has been prosperously developed and been proven to successfully protect against atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%